(untitled) (Fiep Bulletin - online, 2014)
The futsal is an intermittent modality that exposes the athletes a high risk of lesions. The objective of the present study was it of verifying the immunologicals answers of professional athletes of futsal to a period of 7 weeks of training. After this period the athletes presented a non significantly increase of 3% in the leukocytes occasioned per of the increase of 7% of the neutrófilos. There was reduction of the immature neutrophil, eosinophils, lymphocyte and monocytes in 41.5, 18, 4.7 and 6.5%, respectively. In spite of the reduction of the eosinophils, these stayed above the reference values, what reveals that the athletes already came presenting an immunologicals answer previous to the training. We concluded that neutrophil increase happened in this study suggests that there was not occurrence of inflammatory process for muscular offense and the neutrophils they contributed to recovery and muscular adaptation to the training.